Roles of Long Non-coding RNAs in the Development of Aging-Related Neurodegenerative Diseases - Ni, Yu-Qing; Xu, Hui; Liu, You-Shuo (Frontiers in Molecular Neuroscience, 2022)
Ageing-related neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and amyotrophic lateral sclerosis (ALS), are gradually becoming the primary burden of society and cause significant health-care concerns. Ageing is a critical independent risk factor for neurodegenerative diseases. The pathological alterations of neurodegenerative diseases are tightly associated with mitochondrial dysfunction, inflammation, and oxidative stress, which in turn stimulates the further progression of neurodegenerative diseases. Given the potential research value, lncRNAs have attracted considerable attention. LncRNAs play complex and dynamic roles in multiple signal transduction axis of neurodegeneration. Emerging evidence indicates that lncRNAs exert crucial regulatory effects in the initiation and development of ageing-related neurodegenerative diseases. This review compiles the underlying pathological mechanisms of ageing and related neurodegenerative diseases. Besides, we discuss the roles of lncRNAs in ageing. In addition, the crosstalk and network of lncRNAs in neurodegenerative diseases are also explored.